Impact on Soil Bulk Density Caused by Using Buffaloes (Bubalus bubalis) in Timber Skidding - Villalobos-Barquero, Verónica (2019)
The degradation of the soil structure resulting from the harvesting of forest plantations is one of the most important aspects to consider during the production of reforested wood. One of the factors that most accentuate this degradation is the method of extraction used, for this reason, the effect on the soil caused by the constant transit of water buffalo (Bubalus bubalis), during the operation of hauling logs was evaluated. The study was conducted on land owned by small farmers in the Huetar Caribe region of Costa Rica, specifically in Sahara de Batán, Limón. A randomized complete block design was used with two treatments and 4 repetitions per treatment, with which the animals' constant transit along the skid trails was evaluated. The soil bulk density was determined in four skid trails. The soil samples were collected by means of the cylinder method. The normality test was applied, an F test for equality of variances based on two samples and a comparison of means was made. A total of 32 soil samples were studied, of which 16 corresponded to disturbed soil and the remaining 16 to the control. Average bulk density for the disturbed soil 1.071 g/cm3 while the average for the control samples was 1.005 g/cm3. Finally, it was found that both apparent densities were not significantly different (p-value of 0.0824).